PKM PENATAAN TAMAN DI RUANG TERBUKA HIJAU DALAM MENINGKATKAN POLA HIDUP BERSIH - Komarudin, Mamay; Kusuma, Jaka Wijaya; Hamidah, Hamidah; Caesarani, Sarah; Widodo, Wahyu; Munawaroh, Munawaroh (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Green Open Space (RTH) has an important role in creating a healthy, comfortable, and beautiful environment. However, there are still many RTH that are poorly maintained and are not optimally utilized by the community. This Community Service aims to organize parks in RTH to improve a clean lifestyle and community awareness of the importance of a healthy green environment. These activities include improving the landscape of the park, adding ornamental plants and shade trees, and providing sanitary facilities such as adequate trash cans. In addition, socialization and education were carried out to the public about the importance of maintaining cleanliness and sustainability of RTH as part of a healthy lifestyle. The results of this activity show an increase in public awareness and participation in maintaining the cleanliness and sustainability of the park. With a good garden arrangement, RTH can be a comfortable recreational facility while improving the quality of life of the community